AKAD MURABAHAH PADA BANK SYARIAH - Anjar Adrias Pitaloka (At-Taradhi Jurnal Studi Ekonomi, 2015)
Abstract: The emergence of Islamic Banking is triggered by the support of banking expert and Islamic economics and Muslims in the country and abroad which requires that banks practice in accordance with the Quran and Hadith and do not allow usury. In Indonesia, SyariahBank is known since 1992, while in Egypt there have already loan banks with pro?t-sharing system since 1963. In giving ?nancing to customers, most of SyariahBank use Murabahah or commonly called bai al-murabaha. The Akad contains a number of rights and obligations for the parties, namely the Syariah Bank and the customer as the applicant of Murabahah Financing Agreement. The ?nancing required by the customer to purchase goods from a supplier and then sell it to customers by adding the advantagecost (cost plus pro?t) andthis is done through prior negotiations between the bank and the customer concerned.